Professional Burnout Among Administrative Staff at University of Jeddah - Abu Rasayn, Reem Hamoud; Abu El-Enein, Najwa Younes (Journal of Economic, Administrative and Legal Sciences, 2020)
This research aims to measure the level of professional burnout among administrators at the University of Jeddah and know the sources of their professional burnout and to develop recommendations to help overcome the factors leading to it. The research also aims to find out the relationship between professional burnout and some demographic variables. The descriptive-analytical approach was used in the research. A questionnaire was used to measure the level of professional burnout and was applied to a random sample on 51 employees. The results of the study found out that the administrators at the University of Jeddah suffer from a low level of professional burnout, and the results indicated a positive correlation statistically significant between the professional burnout in its three dimensions (emotional stress- inhumanity- personal achievement) and the limited work powers, lack of social relations, work pressure, conflict of values and lack of positive reinforcement. The results also indicated that there were no statistically significant differences in the responses of the study members to the degree of functional combustion in its three dimensions (emotional stress- Inhumanity- personal achievement) administrators attributed to gender, marital status, age, years of experience, educational qualification, salary and administrative level. The study recommended the need to identify sources of pressure to control, and reduce the workload as much as a possible and positive understanding of the pressures of the university work environment and deal with them, and improve the incentives system to obtain an appropriate return of effort and thought during the work.
Keywords: Inhumanity; Emotional stress; Burnout; Saudi Arabia; University of Jeddah